80.4k views
4 votes
Convert Y=0.4(X -3)squared +4 to standard form

1 Answer

3 votes

Answer:


Y=0.4X^2-2.4X+7.6

Explanation:

Given:

The quadratic equation in vertex form is given as:


Y=0.4(X-3)^2+4

The standard form of a quadratic equation is:


y=ax^2+bx+c

Now, in order to convert the given equation into standard form, we have to expand
(X-3)^2 using the binomial expansion given by:


(a-b)^2=a^2+b^2-2ab

Here,
a=X\ and\ b= 3

Therefore,


(X-3)^2=X^2+3^2-2(X)(3)\\(X-3)^2=X^2+9-6X

Now, plug in this expanded form into the original equation. This gives,


Y=0.4(X^2+9-6X)+4

Now, we use distribute 0.4 inside the parenthesis. This gives,


Y=0.4X^2+(0.4*9)-(6X*0.4)+4\\Y=0.4X^2+3.6-2.4X+4\\Y=0.4X^2-2.4X+4+3.6\\Y=0.4X^2-2.4X+7.6

Therefore, the standard form of the given equation is:


Y=0.4X^2-2.4X+7.6

User Mendhak
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.